A revision on Urena lobata L. - Islam, Muhammad; Uddin, Mohammad (International Journal of Medicine, 2017)
The medicinal plant, Urena lobata L. (Malvaceae) is commonly known as aramina fibre, caesarweed or congo jute is widely distributed in Bangladesh. The ethnopharmacological usages of the parts of this plant are antique for the treatment of various diseases. In the recent years, a number of scientific evidences have been seen on its isolated phytochemicals and biological activities. This review offers a current scenario of the U. lobata, emphasized on the phyto-pharmacological findings. A search was made in the electronic databases such as PubMed, Science Direct and Google scholar for the published articles till January 31, 2017. To date, several important flavonoids, glycosides and terpenoids have been isolated from this plant. U. lobata possesses promising biological activities, including antioxidant, inflammatory, antimicrobial, anticancer, anti-diarrheal, anti-diabetic, anti-hyperlipidemic, neuropharmacological etc. U. lobata may be one of the good sources of therapeutic phytochemicals.